Case Report: Influence of BRCA1 germline mutation on treatment-related morbidity of a non-seminomatous germ cell tumor patient - Griesler, Bruno; Schulze, Susann; Kegel, Thomas; Dierks, Christine; Villavicencio-Lorini, Pablo; Eszlinger, Markus; Al-Ali, Haifa Kathrin; Jaekel, Nadja (Frontiers in Oncology, 2025)
We present the case of a 47-year-old male with advanced non-seminomatous germ cell tumor, who was found to carry a heterozygous pathogenic BRCA1 germline variant following molecular testing due to a positive family history. While tumor analysis did not confirm loss of heterozygosity, evidence suggests that BRCA1 haploinsufficiency also increases genomic instability and cancer risk. After pre-phase treatment and the first cycle of chemotherapy, the patient developed prolonged pancytopenia leading to neutropenic sepsis. Subsequent cycles showed a shorter duration of pancytopenia, though it remained significant. A literature review indicates that BRCA1 deficiency may impair bone marrow recovery after chemotherapy, as observed in breast cancer patients, which we hypothesize also applies in this case. After first-line treatment, the patient had a partial response. In case of recurrence, the use of PARP inhibitors should be considered due to the BRCA1 deficiency.